1997
DOI: 10.1093/humrep/12.6.1171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiphospholipid antibodies in women undergoing in-vitro fertilization: role of heparin and aspirin

Abstract: To describe the prevalence of antiphospholipid antibodies in women undergoing in-vitro fertilization (IVF) and to determine if heparin and aspirin affect implantation rates, 191 women with a history of infertility undergoing IVF were prospectively tested for antiphospholipid antibodies. This was a two-centre, non-randomized comparison of women with positive antiphospholipid antibodies receiving heparin and aspirin versus standard treatment. An enzyme-linked immunosorbent assay, with referenced standards and kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1
7

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(88 citation statements)
references
References 6 publications
1
79
1
7
Order By: Relevance
“…Sher et al suggested that heparin and aspirin treatment during IVF cycles in aPL-positive women improves success rates (29), but Kutteh et al showed no difference in implantation or pregnancy rates between primary APS patients pretreated with heparin plus aspirin versus those who received aspirin alone (30). Intravenous immunoglobulin, another treatment option, was used in only 1 of our patients.…”
Section: Discussionmentioning
confidence: 69%
“…Sher et al suggested that heparin and aspirin treatment during IVF cycles in aPL-positive women improves success rates (29), but Kutteh et al showed no difference in implantation or pregnancy rates between primary APS patients pretreated with heparin plus aspirin versus those who received aspirin alone (30). Intravenous immunoglobulin, another treatment option, was used in only 1 of our patients.…”
Section: Discussionmentioning
confidence: 69%
“…Kutteh et al [40] reported a higher implantation rate in the group of women treated with heparin and aspirin (25 vs. 19.4%) but no statistically significant differences were detected in implantation, pregnancy and ongoing pregnancy rates between those who received standard therapy and those treated with heparin and aspirin. In contrast, Sher et al [41] reported that treatment with aspirin and heparin was associated with a significant beneficial effect (rate of ongoing pregnancy: 49 vs. 16%, respectively).…”
Section: Do Apl Have a Pathogenic Role In Infertility?mentioning
confidence: 96%
“…1,6,15 The effect of unfractionated heparin (with aspirin therapy) on in vitro fertilization outcome has been evaluated in several studies, with inconsistent results. [16][17][18][19][20][21] Most of these studies enrolled women with antiphospholipid or other auto-antibodies and were observational in nature. 16,[18][19][20][21] However, one single-center double-blind randomized crossover trial that compared unfractionated heparin 5000 units subcutaneously twice daily and aspirin from the day of embryo transfer with negative pregnancy test or week 14 of pregnancy with placebo in women with recurrent implantation failure and at least one auto-antibody (antiphospholipid antibody or antinuclear antibody) reported no significant difference in pregnancy or implantation rates between treated and placebo cycles (Table 3).…”
Section: Antithrombotic Therapy To Enhance the Likelihood Of Success mentioning
confidence: 99%
“…[16][17][18][19][20][21] Most of these studies enrolled women with antiphospholipid or other auto-antibodies and were observational in nature. 16,[18][19][20][21] However, one single-center double-blind randomized crossover trial that compared unfractionated heparin 5000 units subcutaneously twice daily and aspirin from the day of embryo transfer with negative pregnancy test or week 14 of pregnancy with placebo in women with recurrent implantation failure and at least one auto-antibody (antiphospholipid antibody or antinuclear antibody) reported no significant difference in pregnancy or implantation rates between treated and placebo cycles (Table 3). 17 The results of 3 recent meta-analyses that investigated whether low-molecular-weight heparin (LMWH) administered around the time of implantation improves clinical outcomes in women undergoing assisted reproduction are shown in Table 2.…”
Section: Antithrombotic Therapy To Enhance the Likelihood Of Success mentioning
confidence: 99%